Influência da clorexidina na resistência de união à dentina, morfologia de interface adesiva e nanoinfiltração de cimentos resinosos - Stape, Thiago Henrique Scarabello (2010)
This study focused on adhesive interface morphologic characterization, nanoleakage expression and microtensile bond strength of two resin cements (RelyX ARC and RelyX U100) bonded to human dentin treated with Chlorhexidine. Forty non-carious third molars were ground flat to expose superficial dentine. Composite blocks were luted to the exposed dentine with/without chlorhexidine pre-treatment. Four experimental groups (n=10) were obtained: ARC, U100, ARC/CHX and U100/CHX. Control groups, ARC and U100, were not treated with chlorhexidine. Experimental groups, ARC/CHX and U100/CHX, were pre-treated with chlorhexidine prior to the luting process. After storage in water for 24h, the bonded teeth were sectioned into 0.9 x 0.9 mm cross sectional area sticks. Eight random sticks from each tooth were submitted to microtensile bond test at a crosshead speed of 0.05 mm/min until failure. Two sticks were prepared for hybrid layer evaluation by SEM analysis. Two sticks were immersed in silver nitrate for 24h for nanoleakage evaluation. Nanoleakage samples were carbon coated and examined using backscattered electron mode. Bond strength data were analyzed with analysis of variance (ANOVA) followed by Tukey Test (p<0,05): ARC (42.72 ±4.3)A, ARC/CHX (39.19 ±9.62)A, U100 (12.98 ±3.43)B, U100/CHX (11.97 ±2.6)B. An increase in nanoleakage was observed in groups treated with chlorhexidine for both resin cements. No well- established hybrid layer was identified in the U100 groups. Even though the use of chlorhexidine did not interfere on the bond strength values within each cement, its use along with self-adhesive cements adversely affects the resin-dentin bond morphology which in turn might compromise the resin-dentin bond stability over time.